Human Rights Perspectives on Voluntary Health Workers Nurses Who Work at Government Agencies - Zainal Abidin; Y. Trihoni Nalesti Dewi; Tuntas Dhanardhono (Universitas Katolik Soegijapranata Semarang, 2020)
Nurses as professionals whose existence is recognized by the State have rights that should be fulfilled and protected as professionals and general citizens. The rights that have been guaranteed by various laws and regulations are supposed to remain insufficient to comprehensively accommodate voluntary health worker nurses spreading over the country.Various Indonesian laws and regulations on human rights have guaranteed the rights to work and decent life as well as the rights to recognition, legal certainty, and legal protection. This study aimed to know about the rights to obtain work and decent life viewed from the human rights perspective besides knowing about the guarantee of recognition, legal certainty, and legal protection to voluntary health worker nurses at Bima City, West Nusa Tenggara Province.This study was conducted at Bima City’s General Hospital and Paruga Health Center (Puskesmas). It applied a socio-legal approach and explicative-analytical specification. The data-gathering technique was carried out through interviews with informants, namely the Head of General and Personnel Affairs of Health Office of Bima City, the Head of General and Personnel Affairs of Personnel and Human Resources Office of Bima City, the Head of General and Personnel Affairs of Bima City’s General Hospital and Puskesmas Paruga beside twenty voluntary health worker nurses.The results of this study showed that there was no written legal regulation regarding the procedure of recruiting voluntary health worker nurses in the form of regional regulation nor the Mayor’s Decree that could be used as a legal basis for recruiting voluntary health worker nurses. This led to implications of the fulfillment of the rights to the voluntary health worker nurses, especially in the matters of work and decent life beside guaranteed legal recognition, certainty, and protection.